A TaqMan real – Time RT - PCR assay for detection of Groundnut ringspot virus - Urzêdo Leão, E. [UNESP]; Tavella, L.; Krause-Sakate, R. [UNESP]; Turina, M. (My University, 2016)
Groundnut ringspot virus (GRSV) is a tospovirus species transmitted in a circulative propagative manner by several thrips species. Traditionally, GRSV is detected by enzyme-linked immunosorbent assay (ELISA) and reverse transcription polymerase chain reaction (RT-PCR), so this paper describes a rapid diagnostic system for the reliable detection of GRSV in plants and individual thrips by real-time RT-PCR. Watermelon GRSV infected leaves and fruits, and individual thrips (Frankliniella schultzei) collected from flowers on infected watermelons were used in the test. We designed a GRSV TaqMan assay to efficiently detect GRSV in all samples. The method had high specificity and could distinguish GRSV from the other tospovirus species, like Tomato spotted wilt virus (TSWV), Tomato chlorotic spot virus (TCSV) and Zucchini lethal chlorosis virus (ZLCV). The test will help us to collect epidemiological data for GRSV in plants and thrips worldwide.
Keywords: Frankliniella schultzei; GRSV; Real-time RT-PCR; Tospovirus